The Influence Of Work Discipline and Job Training On Employee Work Productivity At The Petukangan Utara District Office - Erica, Denny; Hoiriah, Hoiriah; Fauziah, Sifa; Mulyadi, Mulyadi; Susila, Mochamad Nandi (SEAN Institute, 2024)
Human resources play a strategic role in determining the success and achievement of company goals. In efforts to realize these objectives, the role of human resources will continue to be optimized to improve their performance for the organization's or company's sustainability. This occurs because the advancement of science and technology still requires human resources to operate, including at the Petukangan Utara Sub-District Office. This research was conducted to determine the influence of work discipline and job training on employee productivity. The analysis tool used was SPSS Statistics 25.0. In this study, 40 respondents were used as research samples, and the research sampling technique used a saturated sampling technique, with a questionnaire used as the data collection tool. This research employed a quantitative approach. The results show that work discipline and job training, both partially and simultaneously, significantly influence employee productivity. The determination test indicates that work discipline and job training influence employee productivity by 83.4%, while other unexamined variables influence the rest.